3D Electrospun Synthetic Extracellular Matrix for Tissue Regeneration. Issue 7 (25th May 2021) - Su, Yingchun; Toftdal, Mette Steen; Le Friec, Alice; Dong, Mingdong; Han, Xiaojun; Chen, Menglin
Abstract : Electrospinning is considered the most versatile micro‐/nanofiber fabrication technology. The electrospun fibers hold high surface area, desired mechanical properties, controlled topography, as well as the ease of biochemical functionalization. The 3D electrospun fibrous structures closely mimic the hierarchical architecture and fibrous features of the extracellular matrices (ECM), which greatly contribute to biomaterials design to stimulate tissue regeneration. Herein, the recent advances in electrospinning technology for 3D production of ECM‐mimicking biomaterial scaffolds are systematically summarized and the applications in neural, cardiac, bone, skin, and vascularized tissue regeneration are thoroughly discussed. Challenges and future scopes related to each field of tissue regeneration are discussed after each subsection. A few examples of liver, kidney, esophageal tissue engineering are also discussed. Finally, the key challenge in the cost‐effective upscale of the electrospinning technique to mature and prevalent industrial applications is outlined. Herein, a systematic, thorough summary of the recent evolutions in electrospinning and its emerging applications for a broad range of tissue regenerations is provided. Abstract : Electrospinning as a versatile technology allows innovative advancement to fabricate 3D fibrous scaffolds that recapitulate the hierarchical architecture and biological features of the extracellular matrices. The emerging applications of these scaffolds in neural, cardiac, bone, skin, vascular, liver, kidney, and esophageal tissue regeneration are reviewed.